Study of atoms, ions and clusters of supported silver by the method of diffuse reflectance electron spectroscopy; 49th International symposium on Molecular spectroscopy, Columbus, USA, 1994 - Pestryakov A. N. Aleksey Nikolaevich (1994, 1994)
В фонде НТБ ТПУ отсутствует